2021
DOI: 10.1186/s12889-021-11318-2
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural disparities of antenatal care in South East Asia: a case study in the Philippines and Indonesia

Abstract: Background The government is obliged to guarantee equal access to antenatal care (ANC) between urban and rural areas. This study aimed to analyze urban-rural disparities in ≥4 ANC visits during pregnancy in the Philippines and Indonesia. Methods The study processed data from the 2017 PDHS and the 2017 IDHS. The analysis unit was women aged 15–49 years old who had given birth in the last 5 years. The weighted sample size was 7992 respondents in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 57 publications
4
31
0
1
Order By: Relevance
“…Previous studies have shown that this condition is caused by living in rural areas, having limited access, and expensive transportation costs to reach high-quality health services. 18 - 21 The results of this study are in line with previous research that living in rural areas makes it possible not to participate in NHI. 7 , 22 …”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown that this condition is caused by living in rural areas, having limited access, and expensive transportation costs to reach high-quality health services. 18 - 21 The results of this study are in line with previous research that living in rural areas makes it possible not to participate in NHI. 7 , 22 …”
Section: Discussionsupporting
confidence: 86%
“…Studies in Afghanistan also report that poor women have lower overall institutional delivery rates in public and private facilities [ 54 ]. Wealth status significantly contributes to antenatal care utilization in Indonesia and the Philippines [ 55 ]. A study in the Philippines reported that increasing health insurance ownership was accompanied by a decrease in inequality in health service utilization [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, more women in rural areas continue to deliver at home despite policies and strategies that promote facility births, and there is evidence that unequal access to services result in unnecessary deaths. 56 Our article therefore provides quantitative data that can be used to improve current approaches that will reduce urban–rural disparities among women.…”
Section: Discussionmentioning
confidence: 99%